Cyprus : Financial Sector Assessment Program Update; Technical Note; Insurance Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2009)
This paper examines the Insurance Regulation and Supervision for Cyprus's Financial Sector Assessment Program. The domestic nonlife market is dominated by motor insurance which accounted for 58 percent of net premiums. All Cypriot business is reinsured with nondomiciled reinsurers. Health insurance is regulated as nonlife business when written as add-ons to accident and sickness or as life business when written with life policies. A number of professional bodies and self-regulatory industry associations complement the regulatory regime for the insurance industry.